Determinação do momento fletor resistente à flambagem lateral com torção de vigas de aço celulares - Laura Maria Paes de Abreu (2011)
In this study, it is obtained the resistance to bending moment of simple supported doubly symmetric cellular steel beams for the limit state of lateral torsional buckling, by finite element analysis using ABAQUS. The numerical analysis considers the non-linear response of the material, the effect of residual stresses and geometrical non-linear behavior of the structure. The results of the analysis are compared with those obtained for similar I-section beams with solid web, allowing to established parameters for the variation of the bending moment response to this limit state. The results are also compared with those given by a design method that is a combination of the ABNT NBR 8800:2008 and the British Standard BS 5950- 1:2000 procedures, applied to solid web beams design. The method consists of the application of the expressions for solid web beams, but considering the geometrical properties of the net section in the center of the holes of the cellular beams. The accuracy of the method is valuated and some practical considerations for the determination of the bending response of cellular beams are presented.